Characteristics of judicial sentence as display of justice legitimation - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2019)
The article examines demands made by law to the sentence. The author reveals attributive qualities of a sentence, namely, legality and validity, following which the motivated character and fairness of a sentence can be assumed. It is proved that the essence of legal force of a sentence consists of removal by the sentence of legal vagueness and final resolution of a legal conflict. The sentence coming into force means that legitimation of justice occurred and the sentence acquired its exceptional nature, irrefutability, prejudgment, compulsory character and feasibility.
Keywords: court; sentence; legality; validity; justice; legal conflict; legal force of a sentence; characteristics of a sentence